2018
DOI: 10.1016/j.cell.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Somatic and Germline Mutation Periodicity Follow the Orientation of the DNA Minor Groove around Nucleosomes

Abstract: Graphical AbstractHighlights d Somatic and germline mutation rates show a 10-bp periodicity in nucleosome-occupied DNA d This periodicity tracks DNA minor groove facing toward and away from the histones d The orientation of the periodicity depends on the mutational processes active in the tissue d This has contributed to the AT/CG 10-bp periodicity in eukaryotic genomes SUMMARYMutation rates along the genome are highly variable and influenced by several chromatin features. Here, we addressed how nucleosomes, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
167
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(180 citation statements)
references
References 85 publications
13
167
0
Order By: Relevance
“…Numerous studies found a strong influence of chromatin features on regional mutation rates. Strikingly, these effects range from the 10 bp periodicity on nucleosomes 23 to the scale of kilo to mega bases caused by the epigenetic state of the genome 21 . To understand how mutational processes manifest on histone-bound DNA, we computed the number of variants on minor groove DNA facing away from and towards histone proteins, and linker DNA between two consecutive nucleosomes.…”
Section: (Epi-)genomic Localisation Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies found a strong influence of chromatin features on regional mutation rates. Strikingly, these effects range from the 10 bp periodicity on nucleosomes 23 to the scale of kilo to mega bases caused by the epigenetic state of the genome 21 . To understand how mutational processes manifest on histone-bound DNA, we computed the number of variants on minor groove DNA facing away from and towards histone proteins, and linker DNA between two consecutive nucleosomes.…”
Section: (Epi-)genomic Localisation Factorsmentioning
confidence: 99%
“…Almost all signatures showed either an increase or a decrease of mutational rates across all nucleosomal states. The only exception to this rule is TS20-N[T>G]T (SBS17a,b), which showed a slight decrease in the outward facing minor groove, while the inwards facing showed elevated mutation rates 23 . TS20 is likely caused by incorporation of dUTP or oxo-dTTP 20 , possibly, but not necessarily, due to 5-FU treatment 31 .…”
Section: Genomic Properties Modulate Signatures With Epigenetic Statmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that translational stability is 135 associated with local variation in mutation rates across the genome, a previously 136 unappreciated aspect. Regions containing rotationally stable nucleosomes, in 137 contrast, are slightly depleted of both mutation types; we didn't perform further 138 analysis on this, as effect of rotational positioning has been comprehensively 139 discussed by Pich et al (2018). A more detailed view with meta-profiles clearly 140 depicts increased SNV and reduced INDEL densities around dyad regions of strong 141 nucleosomes compared with flanking linker regions ( Fig.…”
Section: Datasets Used For Analysis 87mentioning
confidence: 97%